Konsep Perlindungan Anak dalam Pemenuhan Hak-Hak Anak Perspektif Hukum Positif dan Hukum Perdata Islam - Azhar Nur Mawaddah Gulo; Faisar Ananda (Fakultas Syariah dan Hukum Universitas Islam Negeri Sumatera Utara, 2026)
Child protection in Indonesia is increasingly important, along with the increasing cases of domestic violence, exploitation, and post-divorce custody disputes, which often harm children due to conflicting parental interests. Although Indonesia has regulations such as the Child Protection Law, there is still a significant gap between positive legal norms that tend to be oriented towards worldly aspects and Islamic values, which include spiritual dimensions and the afterlife. This study aims to examine in depth the child protection instruments in Islamic civil law as a comprehensive value foundation, and compare them with the provisions of positive Indonesian law. This study uses a qualitative approach with a normative-theoretical literature study approach where data is obtained from authoritative religious texts, state laws and regulations, and secondary legal literature, which are then analyzed using descriptive-analytical analysis methods. The study shows that Islam prioritizes comprehensive child protection from the time of conception until reaching the age of tamyiz through the fulfillment of basic rights, which include the right to life, recognition of lineage, care (hadhanah), maintenance, and livelihood. All these rights are integrated as part of the main objectives of sharia (maqāṣid al-syarī'ah), especially in protecting the soul (ḥifẓ al-nafs) and protecting offspring (ḥifẓ al-nasl). The conclusion of this article emphasizes that child protection in Islamic civil law is a comprehensive instrument because it combines material and spiritual aspects. and positive state law is crucial for strengthening the moral foundation to ensure the overall well-being of children in the future.